2021
DOI: 10.3390/cancers13215485
|View full text |Cite
|
Sign up to set email alerts
|

Role of Isolated Limb Perfusion in the Era of Targeted Therapies and Immunotherapy in Melanoma. A Systematic Review of The Literature

Abstract: Background. Isolated limb perfusion (ILP) is a locoregional procedure indicated by the unresectable melanoma of the limbs. Its complexity and highly demanding multidisciplinary approach means that it is a technique only implemented in a few referral centers around the globe. This report aims to examine its potential role in the era of targeted therapies and immunotherapy by conducting a systematic review of the literature on ILP. Methods. PubMed, Embase and Cochrane Library were searched. The eligibility crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…This represented a major limitation when reviewing the literature, as the response rate of ITM patients treated with only IT could not be extrapolated from most published studies. In our patients who were treated with ILP alone, treatment response and patient survival were consistent with the literature [7,[10][11][12][13]16,[32][33][34][35][36][37], while DFS could not be compared because such information was often unreported in previous studies. In our series, patients who were treated with ILP + IT showed better treatment response but a similar patient survival compared to the literature data on patients treated with IT [21,22,37].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This represented a major limitation when reviewing the literature, as the response rate of ITM patients treated with only IT could not be extrapolated from most published studies. In our patients who were treated with ILP alone, treatment response and patient survival were consistent with the literature [7,[10][11][12][13]16,[32][33][34][35][36][37], while DFS could not be compared because such information was often unreported in previous studies. In our series, patients who were treated with ILP + IT showed better treatment response but a similar patient survival compared to the literature data on patients treated with IT [21,22,37].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggested that combining ILP and IT might offer some advantages over ILP alone in terms of OS, DSS and local DFS. Of note, local toxicity was in accordance with the literature [7,16,[32][33][34][35][36][37], with less than one out of ten patients developing grade III or greater toxicity. At the state of the art, researchers usually include ITM patients among those with distant metastases and not as a stand-alone group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Isolated limb perfusion (ILP) is a technique that was first introduced in 1958 by Creech and Krementz, which consists of the administration of chemotherapy agents exclusively to the involved limb, isolated from the systemic circulation [64]. Chemotherapy drugs are administrated throughout a canulated artery and vein using an extracorporeal bypass circuit, therefore permitting a much higher administration of drugs solely to the isolated limb with a concentration that would not be tolerated systemically [65,66]. Authors have reported overall response rates of 65-100% and complete response rates of up to 65% [67].…”
Section: Isolated Limb Perfusionmentioning
confidence: 99%
“…[149] ILP is a classic approach in patients with limb-inoperable sarcoma and rapidly recurrent metastatic melanoma. [150] ILP therapy of OVs has become an emerging regimen for the treatment of tumor-bearing limbs owing to effective tumor targeting and high titers of ILP-delivered viruses. [151] The ILP delivery of VSV inhibited the growth of extremity osteosarcoma xenografts more potently than the same virus administered intravenously or intratumorally.…”
Section: Other Routes Of Deliverymentioning
confidence: 99%